PERADILAN BERBASIS HARMONI DALAM DALAM GUYUB BUDAYA LAMAHOLOT - FLORES - Karolus KopongMedan (Jurnal Dinamika Hukum, 2012)
This study tried to offer a new theoretic perspective about settlement form of criminal case. Through law anthropolgy study by using etnography approach and hermeneutic analysis method, this study more strengthen the faith that the final goal of every court process is not only to determine who is wrong and who is right, but also to find out the justice and the truth. But, additionally judicial process has to make a harmony or rebuild a social relation among the victims of conflict.  Even, a social harmony that was built is managed generally as individual, and collective context, and as also vertically to the Almighty God. The judicial orientation with rich philosophy of harmony can be applied to social sphere, because actually the harmony value is everybody’s dream in the world.                                         Key words:  judicial, criminal, harmony, adat tradition, Lamaholot society.